Pengaruh Pelatihan dan Kompensasi Terhadap Pengembangan Karir Kepegawaian Badan Pendapatan Daerah Jakarta Pusat - Rahman, Rahul Sulistio; Lahat, Mohammad Amas; Utama, Dani Chandra (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This research was conducted at the Central Jakarta Regional Revenue Agency, the purpose of this research is to find out training and compensation for career development. The research method uses software, namely SPSS Version 20 with a population and sample of 45 employees of the Central Jakarta Regional Revenue Agency. The data used were primary data by distributing a questionnaire through google form to the respondents and data analysis using multiple linear regression analysis, the results of the research for the training variable had  a partial significant effect on career development with a tcal value of 4,567 > 1,681 and a significant of 0.000 < 0.05, then H0 was rejected and H1 was accepted, the compensation variable had a partial significant effect on career development with a value of tcount 2,962 > 1,681 and significant of 0.000 < 0.05, then H0 is rejected and H2 is accepted, while the variables of training and compensation have a significant effect simultaneously on career development with a value of fcal value of 23,516 > from ftable 3.21 and a significant value of 0.000 < 0.05. Based on the results  of the R-Square (R2) determination coefficient test, it is known that 52.8% of the bound variables, namely career development, can be influenced by independent variables, namely training and compensation. While the remaining 47.2% were influenced by other variables that were not studied in this study.